Burden of Public Debt as a Constraint on Nigeria’s Economic Development - Nwokoye, Queendaline; Awa, Felix; Elom, Joseph (PT Mattawang Mediatama Solution, 2025)
The study examined the effect of public debt on the economic development of Nigeria, with the specific objectives of assessing the effect of domestic debt, foreign debt, and debt service on the Human Development Index (HDI). The study adopted an ex-post facto research design, focusing on historical data covering the period from 1999 to 2023. Secondary data were collected from the Central Bank of Nigeria Statistical Bulletin, Debt Management Office reports, National Bureau of Statistics, and United Nations Development Programme reports. Ordinary Least Squares regression was employed in testing the hypotheses. The findings revealed that: domestic debt has a negative but non-significant effect on human development index of Nigeria (β = -0.019818, p = 0.7724); foreign debt has a positive and significant effect on human development index of Nigeria (β = 0.203998, p = 0.0425); debt service has a negative and significant effect on human development index of Nigeria (β = -4.678274, p = 0.0005). In conclusion, regardless of the developmental potential of borrowed funds, the continuous outflow of financial resources in the form of debt servicing erodes gains by limiting the government’s fiscal space to sustain improvements in living standards. The study recommends that lawmakers should prioritize enacting fiscal policies and frameworks that reduce the debt servicing burden by tightening borrowing limits and scrutinizing loan approvals, thereby preventing the diversion of scarce national resources from development-driven programs to excessive debt repayment obligations.